Sustainable battery storage: A hybrid charging solution - Moahmmad Hamdan; Ali Al Zyoud; Homam Al Bakri; Abdelrahman Radwan; Mohammad Ma'aitah; Salman Ajib (Results in Engineering)
Battery energy storage is evolving as an increasingly feasible alternative for self-supported solar power systems in the Levant region, with lead-acid batteries recreating a significant role among the available energy storage solutions. However, these batteries deteriorate over time, influencing their lifespan and performance. This analysis examines the regeneration of a 24-cell bank of 2 V 300 Ah GFM lead-acid batteries. The 2 V cells were reconditioned and assembled into a 48 V battery bank with a comparable 300 Ah capacity through a managed experimental procedure. The outcomes show the effectiveness of the patented regenerative approach, which integrates constant potential, constant current, quick charge, and pulse charge methods. This technique significantly extends battery life by effectively dissolving lead sulfate deposits, balancing cell discrepancies, and restoring battery performance. These findings spotlight the potential of advanced battery reconditioning techniques for extending battery lifespan and improving performance, supporting more sustainable energy storage solutions in solar applications. Finally, the results indicated that the battery voltage of the battery under test was increased by 2.4 %, and its capacity recovery was increased by 2.2 %